Erythropoietin in some blood diseases (thalassemia and leukemia) - Ichiyanagui, Sunio (1966)
Since it was demonstrated that erythropoiesis is subject to hormonal control (1), the search site of production of this factor and the appropriate source from which the erythropoietic hormone could be isolated, has been the subject of multiple investigations. Erythropoietic activity has been found in a variety of fluids including creónlcos plasma, urine (2) milk (3) and isolation of active eritropoyéticamente anterior pituitary (4, 5) material. However, such activity demonstrated in organic fluids in primary form, followed some procedures which showed decrease in capacity utilization of oxygen by the blood (Phenylhydrazine (6), bleeding (7), hypoxia, etc...) In pathological or after administration of cobalt (8) states ; such entity has not been possible to isolate sufficient active fractions to a suitable chemical and biological research. In observations made in large numbers of patients with various types of blood disorders owner trying to erythropoietin plasma, the incorporation of Fe59 into erythrocytes was used as evidence (9) being found in patients with thalassemia and certain cases of leukemia (10), showed marked elevation in their titles. Urine of these patients achieved erythropoietin extracting high power. The above us serves as starting point for the implementation of this work was performed under the direction of DI.